Relevansi Landasan Filosofis Pendidikan dan Pendidikan Nilai dalam Pemikiran Ki Hajar Dewantara dagi Penguatan PPKn - Fazlan Ade Umri; Ade Pranata Ginting; Muhammad Rafli Ashari; Amin Harahap (Pancasila and Civics Education Journal, 2026)
Abstract: This study is motivated by the limited understanding among educators regarding the philosophical foundations of education and the suboptimal integration of value education in learning practices. This study aims to analyze the philosophical foundations of education and the concept of value education from the perspective of Ki Hajar Dewantara’s thought. The research employs a qualitative approach using a literature review method by examining various sources, including books, scientific journal articles, and relevant documents. Data were collected through literature searching, reading, and note-taking techniques, and were analyzed using descriptive qualitative analysis. The findings reveal that the philosophical foundations of education encompass metaphysical, epistemological, and axiological aspects that serve as the basis for determining educational direction, goals, and practices. Value education plays a crucial role in shaping students’ character holistically, covering cognitive, affective, and moral dimensions. Ki Hajar Dewantara’s perspective emphasizes that education is a guiding process to develop learners’ natural potential by maintaining the balance of intellect (cipta), feeling (rasa), and intention (karsa). In conclusion, the integration of philosophical foundations and value education in Ki Hajar Dewantara’s perspective remains relevant in addressing contemporary educational challenges and in fostering individuals with strong character and personality.Keywords: Philosophy of Education, Value Education, Ki Hajar Dewantara, PPKnAbstrak: Penelitian ini dilatarbelakangi oleh masih terbatasnya pemahaman pendidik terhadap landasan filosofis pendidikan serta kurang optimalnya integrasi pendidikan nilai dalam praktik pembelajaran. Penelitian ini bertujuan untuk menganalisis landasan filosofis pendidikan dan konsep pendidikan nilai dalam perspektif pemikiran Ki Hajar Dewantara. Metode yang digunakan adalah studi literatur dengan pendekatan kualitatif melalui pengkajian berbagai sumber pustaka, seperti buku, artikel jurnal ilmiah, dan dokumen relevan. Teknik pengumpulan data dilakukan melalui penelusuran, pembacaan, dan pencatatan, kemudian dianalisis menggunakan metode deskriptif kualitatif. Hasil penelitian menunjukkan bahwa landasan filosofis pendidikan mencakup aspek metafisika, epistemologi, dan aksiologi yang menjadi dasar dalam menentukan arah, tujuan, dan praktik pendidikan. Pendidikan nilai memiliki peran penting dalam membentuk karakter peserta didik secara menyeluruh, tidak hanya pada aspek kognitif, tetapi juga afektif dan moral. Pemikiran Ki Hajar Dewantara menegaskan bahwa pendidikan merupakan proses tuntunan untuk mengembangkan potensi kodrat peserta didik dengan menekankan keseimbangan cipta, rasa, dan karsa. Dengan demikian, dapat disimpulkan bahwa integrasi landasan filosofis pendidikan dan pendidikan nilai dalam perspektif Ki Hajar Dewantara tetap relevan dalam menghadapi tantangan pendidikan modern serta dalam membentuk manusia yang berkarakter dan berkepribadian.Kata Kunci: Filsafat Pendidikan, Pendidikan Nilai, Ki Hajar Dewantara, PPKn